Resveratrol and other Stilbenes: Effects on Dysregulated Gene Expression in Cancers and Novel Delivery Systems - Poltronieri, Palmiro; Xu, Baojun; Giovinazzo, Giovanna (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Trans-resveratrol (RESV), pterostilbene, trans-piceid and trans-viniferins are bioactive stilbenes present in grapes and other plants. Several groups applied biotechnology to introduce their synthesis in plant crops. Biochemical interaction with enzymes, regulation of non-coding RNAs, and activation of signaling pathways and transcription factors are among the main effects described in literature. However, solubility in ethanol, short half-life, metabolism by gut bacteria, make the concentration responsible for the effects observed in cultured cells difficult to achieve. Derivatives obtained by synthesis, trans-resveratrol analogs and methoxylated stilbenes show to be more stable and allow the synthesis of bioactive compounds with higher bioavailability. However, changes in chemical structure may require testing for toxicity. Thus, the delivery of RESV and its natural analogs incorporated into liposomes or nanoparticles, is the best choice to ensure stability during administration and appropriate absorption. The application of RESV and its derivatives with anti-inflammatory and anticancer activity is presented with description of novel clinical trials.
Keywords: stilbenes